174k views
3 votes
Select the correct answer.

Select the correct answer.-example-1

1 Answer

6 votes

Answer:

Option A. is the correct option.

Explanation:

We have to get the simplified form of sin (.6x)-sin(.4x)

As we know the identity sinA- sinB = 2 cos(A+B)/2.sin(A-B)/2

We apply the identity in the given expression

sin(.6x)-sin(.4x) = 2 cos(.6x + .4x)/2.sin(.6x - .4x)/2

= 2 cos(x/2).sin(0.2x/2) = 2 cos(0.5x).sin(0.1x)

Therefore option A is the correct option.

User Apokryfos
by
5.2k points